Drug-Induced Liver Injury Due to Antimicrobials, Central Nervous System Agents, and Nonsteroidal Anti-Inflammatory Drugs - Devarbhavi, Harshad; Andrade, Raúl J. (Seminars in Liver Disease, 2014)
Antimicrobial agents including antituberculosis (anti-TB) agents are the most common cause of idiosyncratic drug-induced liver injury (DILI) and drug-induced liver failure across the world. Better molecular and genetic biomarkers are acutely needed to help identify those at risk of liver injury particularly for those needing antituberculosis therapy. Some antibiotics such as amoxicillin-clavulanate and isoniazid consistently top the lists of agents in retrospective and prospective DILI databases. Central nervous system agents, particularly antiepileptics, account for the second most common class of agents implicated in DILI registries. Hepatotoxicity from older antiepileptics such as carbamazepine, phenytoin, and phenobarbital are often associated with hypersensitivity features, whereas newer antiepileptic drugs have a more favorable safety profile. Antidepressants and nonsteroidal anti-inflammatory drugs carry very low risk of significant liver injury, but their prolific use make them important causes of DILI. Early diagnosis and withdrawal of the offending agent remain the mainstays of minimizing hepatotoxicity.
Keywords: drug-induced liver injury; hepatotoxicity; antibiotics; NSAIDs; central nervous system; antiepileptics; antituberculosis drugs; antifungals